Intravenous Delivery of Lung‐Targeted Nanofibers for Pulmonary Hypertension in Mice. Issue 13 (1st June 2021) - Marulanda, Kathleen; Mercel, Alexandra; Gillis, David C.; Sun, Kui; Gambarian, Maria; Roark, Joshua; Weiss, Jenna; Tsihlis, Nick D.; Karver, Mark R.; Centeno, S. Ruben; Peters, Erica B.; Clemons, Tristan D.; et al.
Abstract: Pulmonary hypertension is a highly morbid disease with no cure. Available treatments are limited by systemic adverse effects due to non‐specific biodistribution. Self‐assembled peptide amphiphile (PA) nanofibers are biocompatible nanomaterials that can be modified to recognize specific biological markers to provide targeted drug delivery and reduce off‐target toxicity. Here, PA nanofibers that target the angiotensin I‐converting enzyme and the receptor for advanced glycation end‐products (RAGE) are developed, as both proteins are overexpressed in the lung with pulmonary hypertension. It is demonstrated that intravenous delivery of RAGE‐targeted nanofibers containing the targeting epitope LVFFAED (LVFF) significantly accumulated within the lung in a chronic hypoxia‐induced pulmonary hypertension mouse model. Using 3D light sheet fluorescence microscopy, it is shown that LVFF nanofiber localization is specific to the diseased pulmonary tissue with immunofluorescence analysis demonstrating colocalization of the targeted nanofiber to RAGE in the hypoxic lung. Furthermore, biodistribution studies show that significantly more LVFF nanofibers localized to the lung compared to major off‐target organs. Targeted nanofibers are retained within the pulmonary tissue for 24 h after injection. Collectively, these data demonstrate the potential of a RAGE‐targeted nanomaterial as a drug delivery platform to treat pulmonary hypertension. Abstract : Peptide amphiphile nanofibers targeted to the receptor for advanced glycation end‐products (RAGE) significantly accumulate within diseased lungs of mice with hypoxia‐induced pulmonary hypertension following intravascular delivery. The targeted nanofibers remain localized to the pulmonary tissue for up to 24 h after injection. PA nanofibers may be effective delivery vehicles to provide targeted therapies for pulmonary hypertension.